Effectiveness of Women-Only Gyms in Increasing Women’s Exercise Participation A Systematic Review - Nayla Khairunissya; Carsiwan; Mutiara Shinta Dewi (Journal of Physical Education Health and Sport, 2025)
Women’s participation in physical activities at the gym is still limited by gender inequality, body stereotypes, and social and psychological barriers, especially in mixed gym environments. This study aims to synthesize scientific evidence on the role of women-only gyms in increasing women’s participation in physical exercise through a Systematic Literature Review. Literature searches were conducted on Scopus with empirical studies selected following the PRISMA 2020 guidelines. A narrative synthesis was used due to the heterogeneity of research designs and participation indicators. The review results show that body image pressure, objectification, appearance anxiety, and issues of access and cost are major barriers to women’s participation, while women-only gyms have the potential to provide a safer, more supportive environment and increase motivation and social support. It was concluded that women-only gyms are a promising environmental strategy to increase women’s exercise participation, although their effectiveness depends on cultural context and program design and requires longitudinal evidence support.